2023
DOI: 10.1007/s11255-023-03568-3
|View full text |Cite
|
Sign up to set email alerts
|

Reno-protective effects of perioperative dexmedetomidine in kidney transplantation: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background and objective There is currently no FDA-approved medical therapy for delayed graft function (DGF). Dexmedetomidine (DEX) has multiple reno-protective effects preventing ischemic reperfusion injury, DGF, and acute kidney injury. Therefore, we aimed to evaluate the reno-protective effects of perioperative DEX during renal transplantation. Methods A systematic review and meta-analysis synthesizing randomized controlled trials (RCTs) from WOS, SCOPU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Difficulties in the treatment of RA are caused by mu that attenuate inflammatory cytokines. Dex is known to induce sedation against inflammatory processes in various tissues, such as the brain, heart [35][36][37][38]. In this study, Dex attenuated the inflammatory effects of cellular resp…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Difficulties in the treatment of RA are caused by mu that attenuate inflammatory cytokines. Dex is known to induce sedation against inflammatory processes in various tissues, such as the brain, heart [35][36][37][38]. In this study, Dex attenuated the inflammatory effects of cellular resp…”
Section: Discussionmentioning
confidence: 61%
“…Difficulties in the treatment of RA are caused by multiple targets that attenuate inflammatory cytokines. Dex is known to induce sedation and protect against inflammatory processes in various tissues, such as the brain, heart, and kidney [ 35 , 36 , 37 , 38 ]. In this study, Dex attenuated the inflammatory effects of cellular responses mediated by multiple inflammatory inputs, including cellular migration and cytokine production in RA-FLSs ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have noted a reduction in post-operative creatinine levels on day 2 of kidney transplantation, but not on day 7 [31], a lower incidence of DGF [11], and less AKI after non-cardiac surgery [32], cardiac surgery [8] or pediatric cardiac surgery [33]. In a more nuanced way, a recent meta-analysis found no dexmedetomidinerelated difference in DGF and acute graft rejection, but a trend towards a more rapid reduction in serum creatinine and urea [34].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Hu, et al included four RCTs and two retrospective studies to show that dexmedetomidine did not reduce the rate of AKI after non-cardiac surgery [8]; however, the results were limited by a small number of trials, low quality of evidence, and lack of renal function parameters. Abuelazm and colleagues performed a meta-analysis evaluating the impact of dexmedetomidine on renal outcomes in kidney transplantation only, without other types of surgery [42]. A recent retrospective cohort study of 2391 patients undergoing non-cardiac surgery suggested that intraoperative dexmedetomidine was associated with a reduced incidence and severity of AKI [43].…”
Section: Discussionmentioning
confidence: 99%